1984
DOI: 10.4039/ent1161041-7
|View full text |Cite
|
Sign up to set email alerts
|

Pest Management of Douglas-Fir Tussock Moth (Lepidoptera: Lymantriidae): A Sequential Sampling Method to Determine Egg Mass Density

Abstract: The sex pheromone of bertha armyworm, Mamestra conjigurata (Walker), was reported to be ( a -1 1-hexadecenyl acetate (Z11-16:Ac) and an unidentified tetradecenyl acetate. Electroantennogram responses of male antennae to synthetic isomeric tetradecenyl acetates and attractancy tests under field conditions showed that the highest number of males were captured with a blend of Z9-14:Ac : Z11-16:Ac in a ratio of 1:19 (Underhill et al. 1977). This blend has been useful for monitoring the relative abundances of berth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Sequential sampling is used for a number of insect species as a tool in surveys for decision making in crop protection (Morris 1955;Waters 1955). It is also a reliable tool in pest management'to reduce sampling effort in monitoring a pest population if economic injury level of the pest species is known (Shepherd et al 1984;Turgeon and Regnibre 1987). Olfert et al (1985) reported that l , 2 , 3 , and 4 wheat midge larvae per kernel ( = 36, 72, 108, and 144 larvae per wheat head) damage 38, 58,78, and 96% of the kernels per head.…”
Section: Resultsmentioning
confidence: 99%
“…Sequential sampling is used for a number of insect species as a tool in surveys for decision making in crop protection (Morris 1955;Waters 1955). It is also a reliable tool in pest management'to reduce sampling effort in monitoring a pest population if economic injury level of the pest species is known (Shepherd et al 1984;Turgeon and Regnibre 1987). Olfert et al (1985) reported that l , 2 , 3 , and 4 wheat midge larvae per kernel ( = 36, 72, 108, and 144 larvae per wheat head) damage 38, 58,78, and 96% of the kernels per head.…”
Section: Resultsmentioning
confidence: 99%
“…Iwao (1975) described a method of sequential sampling to help classify populations relative to a critical density, based on the mean crowding versus mean density relationship mentioned above. This method was used by several authors (Shaw et al 1983;Shepherd et al 1984;Shepherd 1985). Nyrop and Simmons (1984) discussed the errors associated with this method, and suggested that these errors be evaluated with every application.…”
Section: Methodsmentioning
confidence: 99%
“…Egg densities per branch were similar (6.26 and 6.49, respectively, t-testp = 0.79), but because foliage was reduced on the partially defoliated trees (3.69 and 6.70 g of needles per branch, respectively, p < 0.0001), egg density per gram of dry needle weight was significantly higher on the partially defoliated trees (2.63 and 1.20, respectively, p < 0.0001). Shepherd et al (1984) found that distribution of egg masses of Orgyiapseudotsugata (McDunnough) also changed depending on the basic unit selected. However, in contrast to A. gloverana, Condrashoff and Grant (1962) and Mason (1970) found egg mass density of 0. pseudotsugata became concentrated in the lower crowns when upper levels were defoliated.…”
Section: Non-defoliated Treesmentioning
confidence: 98%